Reactivation of Latent Tuberculosis Following COVID-19 and Epstein-Barr Virus Coinfection: A Case Report - Iryna Halabitska; Pavlo Petakh; Valentyn Oksenych; Oleksandr Kamyshnyi (Pathogens)
Background: This case is unique in demonstrating the reactivation of latent tuberculosis (TB) following co-infection with SARS-CoV-2 and Epstein–Barr virus (EBV) in an otherwise healthy young adult. It highlights a rare clinical scenario in which viral immune dysregulation likely facilitated TB progression. To date, few reports have explored the complex interplay between COVID-19, EBV reactivation, and TB in a single patient, particularly with isolated extrapulmonary involvement. Case Presentation: A 24-year-old woman presented with persistent low-grade fever, fatigue, night sweats, unintentional weight loss, and progressive cervical and supraclavicular lymphadenopathy. These symptoms emerged shortly after a moderate COVID-19 infection. Laboratory studies revealed elevated inflammatory markers and pronounced lymphopenia. EBV reactivation was confirmed via serology and PCR. Despite antiviral therapy, symptoms persisted, and imaging revealed necrotic lymphadenopathy. Tuberculous lymphadenitis was diagnosed through fine-needle aspiration cytology and PCR detection of Mycobacterium tuberculosis. The patient was treated with a standard anti-tuberculosis regimen, resulting in clinical, radiological, and immunological improvement. Conclusions: This case underscores the importance of considering latent TB reactivation in patients with persistent lymphadenopathy and recent viral infections, particularly in regions with high TB prevalence. It also emphasizes the need for thorough immunological and microbiological assessment in complex post-viral syndromes. The main clinical takeaway is that COVID-19 and EBV co-infection may create a permissive environment for TB reactivation through immune system compromise.